PERSEPSI KEAMANAN DIRI SISWA KELAS VI SD ADVENTUS KOTA SERANG PASCA EDUKASI SEKSUAL BERSAMA YAYASAN KAKAK AMAN INDONESIA - Yulianti, Fena; Pertiwi, Fitri; Fatimah, Nining (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sexual violence against children is a serious issue that requires early prevention through appropriate education. Sex education for children does not focus on sexual activity, but on understanding the body, personal boundaries, and self-protection skills. This study aims to describe the perceptions of self-safety among pupils at Adventus Primary School in Serang City following their participation in a sexual education programme run by the Kakak Aman Indonesia Foundation. The study employed a descriptive qualitative approach, with data collected through in-depth interviews with eight Year 6 pupils at Adventus Primary School. Data analysis was conducted inductively to comprehensively describe changes in the pupils’ understanding and attitudes. The results of the study indicate that sex education has a positive impact on pupils’ understanding, attitudes, and readiness to maintain their personal safety. The pupils were able to explain the concept of bodily autonomy, identify private body parts, distinguish between safe and unsafe touch, and understand self-protection measures such as saying “no”, moving away from risky situations, and reporting to a trusted adult. In addition to increased knowledge, the pupils also demonstrated the courage to refuse inappropriate behaviour and an awareness of the need to seek help. Interactive learning methods involving games and discussions have been shown to enhance pupils’ engagement with and understanding of the subject matter. These findings confirm that sex education plays a vital role in raising awareness, knowledge and self-protection skills among primary school pupils as a preventive measure against sexual violence against children. Therefore, sex education programmes need to be implemented on an ongoing basis and tailored to the developmental characteristics of children.